Exclosures improve degraded landscapes in the sub-humid Ethiopian highlands: the Ferenj Wuha Watershed - Adem, Anwar A.; Mekuria, Wolde; Belay, Y.; Tilahun, Seifu A.; Steenhuis, T. S. (Elsevier, 2020)
Land resources in developing countries are facing intense degradation due to deforestation and subsequent loss of organic matter from continuous tillage that causes soil erosion and gulley formation. The Ethiopian highlands are especially and severely affected. One of the land and water management practices to counteract this problem, fenced areas to prevent livestock access (called exclosures), has been in practice for the last few decades in the semi-arid highlands of Ethiopia but its effect on degraded landscapes has not been well researched – especially in the sub-humid and humid highlands. The aim of this study is to evaluate the effects of exclosures on improving degraded landscapes in the sub-humid highlands. The research was carried out in the Ferenj Wuha watershed, in the northwestern sub-humid Ethiopian highlands, where land and water management practices were implemented starting in 2011. Vegetation was inventoried and aboveground biomass, carbon and nutrient stock determined for communal grazing land, exclosures and for other uses. In addition, soil samples were collected for nutrient analysis. Our results show that exclosures have a richer and more diverse set of plant species compared to communal grazing land. Establishment of an exclosure also enhanced organic carbon, total nitrogen and available phosphorus. Over a six-year period, aboveground biomass increased by 54 Mg ha 1 (or 81%) at the watershed scale because of the conversion of communal grazing land to exclosures. The improvement in soil nutrients due to exclosures, in turn, increased carbon and nutrient stock. The results support regeneration of degraded landscapes by restoring vegetation, soil fertility, carbon and nutrient stocks in the Northwestern highlands of Ethiopia. However, additional research is required to more accurately quantify these improvements because current research efforts that sample only the surface soils seem to indicate that the capacity of exclosures to increase soil carbon storage is decreasing when annual rainfall is increasing.